1998
DOI: 10.1002/(sici)1096-9861(19980720)397:1<41::aid-cne4>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Striatin, a newly identified calmodulin-binding protein in the rat brain: An in situ hybridization and immunocytochemical study

Abstract: Striatin, a 110-kDa protein, is the first member of the tryptophane-aspartate repeat protein family known to bind calmodulin in the presence of Ca2+. We examined the distribution of striatin and its mRNA in the rat central nervous system (CNS) by using immunocytochemistry and in situ hybridization, respectively. Striatin immunostaining and mRNA labeling patterns are generally concordant. Regions showing the most intense staining are the dorsal striatum, nucleus accumbens (anterior and shell parts), olfactory t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 52 publications
(66 reference statements)
0
13
0
Order By: Relevance
“…It is important to consider the subcellular localization of the PRO11 WD40 protein because mammalian homologues, such as striatin, SG2NA, and zinedin, are neuronal proteins that are strictly expressed in the somatodendritic compartments. These are found in the cytosol and are also associated with membranes (11,16,38).…”
Section: Resultsmentioning
confidence: 99%
“…It is important to consider the subcellular localization of the PRO11 WD40 protein because mammalian homologues, such as striatin, SG2NA, and zinedin, are neuronal proteins that are strictly expressed in the somatodendritic compartments. These are found in the cytosol and are also associated with membranes (11,16,38).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, striatin, an intracellular, neuronal protein endowed with multiple protein-protein interaction domains, has a very peculiar localization, being restricted to CNS structures primarily related to locomotor activity (Castets et al, 1996;Bartoli et al 1998Bartoli et al , 1999aMoqrich et al, 1998). Furthermore, it displays a polar subcellular distribution, being strictly localized to the somato-dendritic compartment (Castets et al, 1996;Kachidian et al, 1998;Salin et al, 1998;). On the one hand, the transient blockade of striatin synthesis in embryonic motoneurons resulted in the severe impairment of dendritic growth.…”
Section: Discussionmentioning
confidence: 99%
“…The structure and composition of axons and dendrites are quite different, particularly concerning their respective plasma membranes, cytoskeleton (Gunning et al, 1998;Baas, 1999), and proteins involved in vesicular traffic, such as motor proteins (Foletti et al, 1999;Burack et al, 2000). Striatin is a neuronal, intracellular protein strictly expressed in the somato-dendritic compartment, including spines, of subsets of neurons: thus, it can be considered as a marker of neuronal polarity (Castets et al, 1996;Kachidian et al, 1998;Salin et al, 1998). Found in the cytosol as well as associated with membranes, striatin is endowed with protein-protein association modules as diverse as a caveolin-binding motif, a coiled-coil structure, a Ca 2Ï© -calmodulin-binding amphiphilic helix, and a WD-repeat domain (Castets et al, 1996;Bartoli et al, 1998Bartoli et al, , 1999bMoqrich et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…For example, striatin is highly abundant in the postsynaptic densities of neurons in rat brains (6,8), and striatin antisense experiments in rat neuronal cell culture (9) resulted in a decrease in the number of observed neurites. Recently, it has been shown that Rho kinase phosphorylation of vimentin on Ser-71 and Ser-38 results in neurite retraction (31), whereas Rho kinase inhibitors produce irregular neurite outgrowth.…”
Section: Fig 2 Mammalian Mob1 Is Covalently Modified In Vivomentioning
confidence: 99%
“…However, more recent studies (7) indicate that SG2NA, like striatin (6,7), is primarily localized to the cytosol and the membrane. Striatin has been detected by immunofluorescence throughout neuronal dendrites, especially in the post-synaptic densities of neuronal dendritic spines (6,8). Moreover, striatin contains two polybasic domains that are absent in SG2NA and may facilitate association with the post-synaptic membrane (6).…”
mentioning
confidence: 99%